Association between dry eye and traditional Chinese medicine body constitutions: A Taiwanese adults study. Issue 2 (15th January 2021) - Chen, Shih-Lin; Hsueh, Kuang-Chieh; Tang, Pei-Ling
Abstract : Abstract: In the theory of traditional Chinese medicine (TCM), except for the balanced constitution, other constitutions are unbalanced and may lead to susceptibility to certain diseases. This study made the first efforts to explore the relationship between TCM constitutions and the dry eye condition. This cross-sectional study collected information from 2760 subjects aged 30 to 70 years who had participated in a questionnaire survey conducted by Taiwan Biobank (TWB) in 2012 to 2017. The questionnaire included questions on basic demographic characteristics, chronic diseases, depression, blood lipid levels, lifestyles, and drug allergies, as well as a TCM constitution scale developed by a research team of TCM constitution and syndrome at China Medical University College of Chinese Medicine. Unadjusted and stratified multiple logistic regression analyses were performed to explore the relationships between TCM constitutions and dry eye. The analysis revealed that subjects falling into the constitution category of Yang deficiency, Yin deficiency, or Phlegm stasis were more likely to develop dry eyes (crude odds ratio [OR] = 1.741, 95% confidence interval [CI] = 1.361–2.227; crude OR = 2.4821, 95% CI = 1.968–3.131; and crude OR = 2.082, 95% CI = 1.597–2.714, respectively). After adjusting for important risk factors (demographic characteristics, chronic diseases, blood lipid levels, lifestyles, depression, and drug allergies), subjects with an unbalanced constitution were 1.6 to 2.5 times more likely to develop dry eye than those with a balanced constitution. These results confirm a high correlation of TCM constitution with dry eye. Considering that the current treatment outcome is not fully satisfactory to the patients with dry eyes, integration of TCM and Western medicine may be an alternative treatment option. Individualized treatments and lifestyle recommended should be provided to patients with different TCM constitutions to alleviate dry eye symptoms.